Inclusion as a necessity of current education - Marín Granados, Laura Yazmín; Marin Granados, Liliana Yadira (Revista Minerva, 2022)
Over time, people with disabilities have experienced situations of exclusion of different intensity that have hindered the enjoyment and exercise of their rights as citizens in different areas of life. Inclusion from the educational context must ensure that each learner feels valued and respected and can enjoy a clear sense of belonging. However, many obstacles stand in the way of that ideal. Discrimination, stereotypes and alienation exclude many. Therefore, the way educational systems are conceived is decisive. This article aims to take a look at the need to promote inclusion in general and education in particular, so that everyone can enjoy the right to education, guaranteeing respect for diversity and the quality of the educational process. The methodology is worked from the implementation of theoretical and empirical methods that allowed to analyze the information and synthesize it in a new theory. The results will be focused on assuming inclusion as a necessity of current education and that the teaching staff and the entire educational community feel their responsibility in this process and get involved.
Keywords: Integration; Inclusion; Educational Inclusion